PENGARUH TERPAAN PARIWISATA DAN MEDIA MASSA TERHADAP PRESTASI BELAJAR PESERTA DIDIK MTSN PANGANDARAN KABUPATEN CIAMIS - Patimah Patimah (IAIN Ponorogo, 2013)
Abstract: The tourism resort as a social environment and mass media as a non- social environment will affect student learning outcomes. Studies on those effects on learning achievement seem to be essential to do. By employing descriptive and explanatory methods, this study attempted to investigate the influence of tourism and mass media exposure on student achievement. The results showed that firstly, the average exposure to tourism was at a high level with the score of 144 laid on the high range of 138-160; secondly, mass media exposure was in the rate of high level with the score of 141 between the range of 138-160 (high); thirdly, student achievement on average was at a moderate level with the score of 75 laid between the range of 56-75 (moderate); the fourth, there was any significant effect of tourism exposure on student achievement at the high level with the value of r = 0.66 ranging between .61 to .80 (high); the fifth, there was any significant effect of mass media exposure on student achievement at the high level with the value of r = 0.71 ranging between .61 to 0 , 80 (high); the sixth, a significant difference between mass media and tourism exposures on student achievement was at the high level of closeness with the score value of r = 0.75 laid between 0.61 to 0.80 (high). امهيرثأت امله -ةيعامتجلاا يرغ ةئيبلاك - ملاعلاا لئاسوو - ةيعامتجلاا ةئيبلاك - ةيحايسلا ةئيبلا :صخلم اذه فشتكا .اباّ ذج اعوضوم بلاطلا ملعت ةجيتن ىلع امهيرثأت في ةساردلا نوكتو .بلاطلا ملعت ةجيتن ىلع ةجيتن ىلع )اعم( ملاعلإا لئاسوو يحايسلا روهظلا يرثأت ىدم ينايبلاو يفيكلا ثحبلا بولسأب – ثحبلا ةجيتنلاب ةيلاعلا ةجردلا في ةلداعلماب ةيحايسلا ةباصلإا تناك )1 : ةيلاتلا جئاتنلاب ةساردلا تتأو .بلاطلا ملعت 141ةميقلاب ةيلاعلا ةجردلا في ةلداعلماب ملاعلإا لئاسو ةباصإ تناك )2 .)ةيلاع( 160-138 ينب نوكت 144 ينب نوكت 75 ةميقلاب ةطسوتلما ةجردلا في نوكي ةلداعلماب بلاطلا زانجإ )3. )ةيلاع( 160-138 ينب نوكت ةجردلا في بلاطلا ملعت زانجإ ىلع ةيحايسلا ةباصلإا نم ىنعم وذ يرثأتلا دجوي )4 .)ةطسوتم( 75-56 لئاسو ةباصإ نم ىنعم وذ يرثأتلا دجوي )5 ،)ةيلاع( 0,80-0,61 ينب نوكت 0,66 = r ةميقلاب ةيلاعلا ، )ةيلاع( 0,80-0,61 ينب نوكت 0,71 =r ةميقلاب ةيلاعلا ةجردلا في بلاطلا ملعت زانجإ ىلع ملاعلإا ةجردلا في بلاطلا ملعت زانجإ ىلع )اعم( ملاعلإا لئاسو و ةيحايسلا ةباصلإا ينب ىنعم وذ يرثأتلا دجوي )6.)ةيلاع( 0,80 – 0,61 ينب نوكت 075=r ةميقلاب ةيلاعلا